2021
DOI: 10.21273/horttech04765-20
|View full text |Cite
|
Sign up to set email alerts
|

Leaf-tissue Nutrient Dynamics in Mature Muscadine Cultivars Carlos and Noble in Georgia and North Carolina

Abstract: More than 3000 acres of commercial muscadine (Vitis rotundifolia) vineyards exist in the southeastern United States. The muscadine wine industry is generating an economic impact of $1 billion in North Carolina alone. Muscadines have been cultivated since the 1800s, but muscadine vineyard fertilizer programs, tissue sampling, and nutrient sufficiency ranges continue to be based on anecdotal knowledge. While seasonal changes in tissue nutrient concentration are well documented in bunch grape (Vitis vinifera), qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 21 publications
2
1
0
Order By: Relevance
“…While the location of the sample (either primary shoot or opposite of a cluster) did not have an impact, the tissue type (petiole vs. full leaf) showed difference in content and variability between mobile and less mobile nutrients. This was reported previously in Vitis vinifera [5,10,29,33] and muscadines [26,32]. Generally, lower variability was observed when samples were taken as whole leaf samples.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…While the location of the sample (either primary shoot or opposite of a cluster) did not have an impact, the tissue type (petiole vs. full leaf) showed difference in content and variability between mobile and less mobile nutrients. This was reported previously in Vitis vinifera [5,10,29,33] and muscadines [26,32]. Generally, lower variability was observed when samples were taken as whole leaf samples.…”
Section: Discussionsupporting
confidence: 81%
“…Petiole P and K were mostly above the recommended sufficiency ranges [3], while full leaf P and K content were above or within the range with the progression of the season. Similar trends were found in a recent survey of muscadine tissue nutrient content across two states [26], suggesting a reevaluation and update of the recommended ranges for most nutrients. K was an exception in our study, as it showed lowest content during fruit set in full leaf samples.…”
Section: Nutrient Contentsupporting
confidence: 76%
See 1 more Smart Citation